Metabolism of municipal solid waste (msw) leachate for acetic and butyric acid conversion by C.Butyricum. - Tajarudin, Husnul Azan (Universiti Sains Malaysia, 2017)
Leachate is a contaminated liquid generated from landfill, imposing a devastating effect to the environment. This study focuses on bioconversion of treated lenchate to acetic and butyric acid by Clostridium butyricum NCIMB 7423 which aims to solve the leachate treatment problem and at the same time produce value added product from the treatment.